An effective vaginal gel to deliver CRISPR/Cas9 system encapsulated in poly (β-amino ester) nanoparticles for vaginal gene therapy - Niu, Gang; Jin, Zhuang; Zhang, Chong; He, Dan; Gao, Xueqin; Zou, Chenming; Zhang, Wei; Ding, Jiahui; Das, Bhudev C.; Severinov, Konstantin; Hitzeroth, Inga Isabel; Debata, Priya Ranjan; et al. (EBioMedicine, 2020)
Gene therapy has held promises for treating specific genetic diseases. However, the key to clinical application depends on effective gene delivery. Using a large animal model, we developed two pharmaceutical formulations for gene delivery in the pigs’ vagina, which were made up of poly (β-amino ester) (PBAE)-plasmid polyplex nanoparticles (NPs) based two gel materials, modified montmorillonite (mMMT) and hectorite (HTT). By conducting flow cytometry of the cervical cells, we found that PBAE-GFP-NPs-mMMT gel was more efficient than PBAE-GFP-NPs-HTT gel in delivering exogenous DNA intravaginally. Next, we designed specific CRISPR/SpCas9 sgRNAs targeting porcine endogenous retroviruses (PERVs) and evaluated the genome editing efficacy in vivo. We discovered that PERV copy number in vaginal epithelium could be significantly reduced by the local delivery of the PBAE-SpCas9/sgRNA NPs-mMMT gel. Comparable genome editing results were also obtained by high-fidelity version of SpCas9, SpCas9-HF1 and eSpCas9, in the mMMT gel. Further, we confirmed that the expression of topically delivered SpCas9 was limited to the vagina/cervix and did not diffuse to nearby organs, which was relatively safe with low toxicity. Our data suggested that the PBAE-NPs mMMT vaginal gel is an effective preparation for local gene therapy, yielding insights into novel therapeutic approaches to sexually transmitted disease in the genital tract. This work was supported by the National Science and Technology Major Project of the Ministry of science and technology of China (No. 2018ZX10301402); the National Natural Science Foundation of China (81761148025, 81871473 and 81402158); Guangzhou Science and Technology Programme (No. 201704020093); National Ten Thousand Plan-Young Top Talents of China, Fundamental Research Funds for the Central Universities (17ykzd15 and 19ykyjs07); Three Big Constructions—Supercomputing Application Cultivation Projects sponsored by National Supercomputer Center In Guangzhou; the National Research FFoundation (NRF) South Africa under BRICS Multilateral Joint Call for Proposals; grant 17–54–80078 from the Russian Foundation for Basic Research.